Aromaterapi zingiber officinale dalam mengurangi emesis gravidarum pada ibu hamil trimester I - Mahfuzhah Deswita Puteri; Darmayanti Wulandatika; Siti Fatimah (Holistik Jurnal Kesehatan, 2026)
Background: Changes in pregnant women can cause discomfort during pregnancy, one of which is nausea and vomiting. Nausea and vomiting are common pregnancy complications. This study is novel in that it examines the effect of ginger aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester. Purpose: To determine the effect of ginger aromatherapy in reducing nausea and vomiting in pregnant women in the first trimester. Method: This study used a quasi-experimental design with a single-group pre-test-post-test. The population was all pregnant women in the first trimester of pregnancy in the Sungai Mesa Community Health Center working area from January to August 2023. Sampling used non-probability sampling, resulting in 15 participants. The independent variable in this study was ginger aromatherapy, while the dependent variable was nausea and vomiting in pregnant women in the first trimester. The checklist used in this study was to obtain data on emesis gravidarum variables, which were assessed using the Pregnancy-Unique Quantification of Emesis/Nausea (PUQE) emesis measurement tool within 24 hours. Bivariate analysis used the Mann-Whitney test. Results: Nausea and vomiting in pregnant women in the first trimester before receiving ginger aromatherapy had an average score of 12.9, and after receiving ginger aromatherapy, the average score was 6.20. The Wilcoxon test showed a significance value of 0.001 (<0.05), indicating that ginger aromatherapy is effective in reducing nausea and vomiting in pregnant women in the first trimester. Conclusion: Ginger aromatherapy is effective in reducing hyperemesis gravidarum in pregnant women in the first trimester, with a p-value of 0.000. Suggestion: Further research can examine other therapies to reduce nausea and vomiting in pregnant women, by trialing one therapy or comparing them to determine which method is most effective.   Keywords: Aromatherapy; Emesis Gravidarum; Pregnant Women in the First Trimester; Zingiber Officinale.